MOVING ON WITH GLOBAL SCALES: A STUDY OF ’LOCKED DOWN’ FEMININE LIVES IN NORTH KERALA - A. V., Sujatha (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The paper presents the study conducted among the village women in my everyday life, my friends, colleagues, relatives, the mothers of my students and also the women in my neighbourhood. It uncovers the impact of the pandemic on the locked-down lives of women from the villages of Kasaragod and Kannur districts of North Kerala, the Southern state of India. As Kerala has been applauded for its high rate of literacy among both the sexes and its globally praised health indicators, a glance into the pandemic-stricken lives of ordinary women and the academic interest to see if the women of my locality reflect the global or national trend in their lives during the pandemic is worth studying with its interdisciplinary implications.